2016
DOI: 10.5603/dk.2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

Active screening for diabetic foot — assessment of health care professionals’ compliance to it

Abstract: Background. The strategy of care for chronic diabetic complications prevention includes appropriate organization and education of healthcare professionals. Despite the availability of skilled medical staff, there is insufficient information about the feet examination in standard practice. We evaluated the personnel's compliance in the context of following the guidelines for foot examination. Materials and methods. We retrospectively analyzed 290 questionnaires from patients with diabetes mellitus (54.13% women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The study by Hirsch et al [ 37 ] states that physicians who use only reported IC for detection of LEAD are unlikely to diagnose 85–90% of LEAD patients. Sutkowska et al [ 38 ] pointed out that there is a low awareness of patients, regarding the possible manifestations of LEAD, and that even medical staff appear to give the minimum attention to some examinations such as, for example, foot examination. The ABI value indicates the ratio between systolic blood pressure measured at the ankle and systolic blood pressure measured at the brachial artery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Hirsch et al [ 37 ] states that physicians who use only reported IC for detection of LEAD are unlikely to diagnose 85–90% of LEAD patients. Sutkowska et al [ 38 ] pointed out that there is a low awareness of patients, regarding the possible manifestations of LEAD, and that even medical staff appear to give the minimum attention to some examinations such as, for example, foot examination. The ABI value indicates the ratio between systolic blood pressure measured at the ankle and systolic blood pressure measured at the brachial artery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathologies that are risk factors for the occurrence of a diabetic foot occur quite common in diabetic patients, e.g., in a study conducted in Wroclaw (Poland), it was found that 7.28% of diabetic patients have peripheral neuropathy; 35.37%, calluses; 24.2%, foot deformities; and 17.39%, features of the pathology of arterial vessels [51] A study revealed that diabetic foot syndrome may result in lower-extremity amputation [52].…”
Section: The Outcome Of Lower Limb Amputation Among Patientsmentioning
confidence: 99%
“…4 It is believed that one in 4 patients with diabetes will develop a foot ulcer. 5 Around 56% of these ulcers can get infected and lead to some form of amputation. 6,7 It thus becomes quite essential to screen the diabetic patients who are at risk of foot problems that can lead to amputation.…”
Section: Introductionmentioning
confidence: 99%